THE EFFECT OF EXCHANGE RATE, CONSUMPTION, AND GDP ON INDONESIAN RUBBER EXPORTS BY MAIN DESTINATION COUNTRY - Lisdiani, Ilfy; Nikensari, Sri Indah; Iranto, Dicky (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
As one of the largest natural rubber exporters in the world, Indonesia has global potential to conquer the rubber export market. This condition is indicated by the high value of Indonesia's natural rubber exports to the global market. Based on the current world natural rubber export data of 64.8%, this value is of course controlled by the world's two largest rubber exporters, one of which is Indonesia at 28.8%. This study aims to determine the effect of exchange rates, consumption, and gross domestic product on Indonesian rubber exports according to the main destination countries. The method used in this study is the panel data regression method of the five main destination countries for Indonesian rubber exports, namely the United States, Japan, China, India, and South Korea in the 2013-2019 period with a fixeffect model. This data is secondary data obtained through a trade map and world bank and processed using Eviews 11. The results showed that consumption and exchange rate variables had a significant effect, while the GDP variable had no significant effect on rubber exports in Indonesia by destination country.